2011
DOI: 10.1097/pas.0b013e31820ca624
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Prognostic Factors in Stage I Leiomyosarcoma of the Uterus

Abstract: Uterine leiomyosarcomas (Ut-LMSs) are aggressive tumors with an overall poor prognosis (15% to 25% 5-year survival rate). However, patients with stage I Ut-LMSs are reported to have a relatively better outcome when compared with the overall group with a 5-year survival rate ranging from 25% to 75%. The purpose of this study was to evaluate the histopathologic parameters that may impact outcome in stage I Ut-LMSs. Twenty-seven patients with stage I Ut-LMSs were identified from the files of 5 tertiary care hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 0 publications
2
33
0
1
Order By: Relevance
“…Factors associated with poor prognosis have not been consistent in different series of uterine leiomyosarcomas [7,8,10,22,32]. However, in a recent study of 245 leiomyosarcomas confined to the uterus [11], tumor size and mitotic index were found to be significant prognostic factors and allowed for separation of patients into 3 risk groups with marked differences in prognosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Factors associated with poor prognosis have not been consistent in different series of uterine leiomyosarcomas [7,8,10,22,32]. However, in a recent study of 245 leiomyosarcomas confined to the uterus [11], tumor size and mitotic index were found to be significant prognostic factors and allowed for separation of patients into 3 risk groups with marked differences in prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…However, carcinosarcomas are no longer considered uterine sarcomas but metaplastic forms of endometrial carcinomas or tumors undergoing divergent differentiation [5]. Most of the reported series of pure uterine sarcomas have focused on specific histologic types, such as leiomyosarcomas [6][7][8] or endometrial stromal sarcomas [9], and very few comparative studies including all major clinicopathologic categories have been reported [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Correct classification is important as currently prognosis of its malignant counterpart, leiomyosarcoma, is dismal even when confined to the uterus at time of diagnosis. [1][2][3] Interestingly, the recent AJCC staging system of soft tissue sarcomas has been recommended to stage uterine malignant smooth muscle tumors. However, it is important to note that several studies have shown no advantage of this system over the old FIGO staging system to improve prediction of overall survival in patients with leiomyosarcoma, [4][5][6][7] whereas neither system is ideal in classifying patients into four clinically significant stages.…”
mentioning
confidence: 99%
“…Olgularımızdan 3'ünde tanı anında servikste, 2'sinde overde, 2'inde parametriyumda, 2'inde de omentumda tutulum mevcuttu. LMS'lar oldukça agresif seyirli neoplazilerdir ve konvansiyonel iğsi hücreli LMS'ların epiteloid ve miksoid LMS'lara göre daha iyi prognoza sahip olduğu gösterilmiştir (8). Lusby ve ark.…”
Section: Discussionunclassified